Deghosting, Demultiple, and Deblurring in Controlled-Source Seismic Interferometry - Joost van der Neut; Maria Tatanova; Jan Thorbecke; Evert Slob; Kees Wapenaar (International Journal of Geophysics)
With controlled-source seismic interferometry we aim to redatum sources to downhole receiver locations without requiring a velocity model. Interferometry is generally based on a source integral over cross-correlation (CC) pairs of full, perturbed (time-gated), or decomposed wavefields. We provide an overview of ghosts, multiples, and spatial blurring effects that can occur for different types of interferometry. We show that replacing cross-correlation by multidimensional deconvolution (MDD) can deghost, demultiple, and deblur retrieved data. We derive and analyze MDD for perturbed and decomposed wavefields. An interferometric point spread function (PSF) is introduced that can be obtained directly from downhole data. Ghosts, multiples, and blurring effects that may populate the retrieved gathers can be locally diagnosed with the PSF. MDD of perturbed fields can remove ghosts and deblur retrieved data, but it leaves particular multiples in place. To remove all overburden-related effects, MDD of decomposed fields should be applied.